Fear-related factors in patients undergoing electroconvulsive therapy at psychiatric wards - Ranjbar, F; Tamizi, Z; Alavi- Majd, H (Advances in Nursing & Midwifery, 2009)
Background Electroconvulsive therapy (ECT) is an effective intervention with no medication in many psychiatric patients. Since electricity and convulsions are evident in this method, many patients feel an unwanted fear from it, leading to noncompliance. Purpose This descriptive study was conducted to assess fear-related factors in patients undergoing ECT in psychiatric wards of hospitals affiliated to Shaheed Beheshti Medical University in 2008. Methods 200 patients were selected with nonrandomized sampling method. A questionnaire was used for data collection, validated and made reliable by content and internal consistency methods respectively. Data were collected by self-report method. Results 99.5% of the subjects reported fear from the therapy while 0.5% experienced no fear. Factors related to procedures during the therapy were the most fearful ones in this regard. Conclusion Most subjects experienced fear during electroconvulsive therapy more than what has been reported in other studies. The fear from the procedure of the therapy was the highest, which is congruent with past evidence. It can be concluded that education and counseling can reduce the fear to make the therapy more comfortable and acceptable for the patients. Keywords: Fear, Electroconvulsive therapy, Psychiatry.